AtSIG6 and other members of the sigma gene family jointly but differentially determine plastid target gene expression in Arabidopsis thaliana - Bock, Sylvia; Ortelt, Jennifer; Link, Gerhard (Frontiers in Plant Science, 2014)
Plants contain a nuclear gene family for plastid sigma factors, i.e. proteins that associate with the “bacterial-type” organellar RNA polymerase and confer the ability for correct promoter binding and transcription initiation. Questions that are still unresolved relate to the “division of labour” among members of the sigma family, both in terms of their range of target genes and their temporal and spatial activity during development. Clues to the in vivo role of individual sigma genes have mainly come from studies of sigma knockout lines. Despite its obvious strengths, however, this strategy does not necessarily trace-down causal relationships between mutant phenotype and a single sigma gene, if other family members act in a redundant and/or compensatory manner. We made efforts to reduce the complexity by genetic crosses of Arabidopsis single mutants (with focus on a chlorophyll-deficient sig6 line) to generate double knockout lines. The latter typically had a similar visible phenotype as the parental lines, but tended to be more strongly affected in the transcript patterns of both plastid and sigma genes. Because triple mutants were lethal under our growth conditions, we exploited a strategy of transformation of single and double mutants with RNAi constructs that contained sequences from the unconserved sigma region (UCR). These RNAi/knockout lines phenotypically resembled their parental lines, but were even more strongly affected in their plastid transcript patterns. Expression patterns of sigma genes revealed both similarities and differences compared to the parental lines, with transcripts at reduced or unchanged amounts and others that were found to be present in higher (perhaps compensatory) amounts. Together, our results reveal considerable flexibility of gene activity at the levels of both sigma and plastid gene expression. A (still viable) “basal state” seems to be reached, if 2 - 3 of the 6 Arabidopsis sigma genes are functionally compromised.